2021
DOI: 10.1161/jaha.121.023227
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Supplementation Mitigates Perivascular Adipose Inflammation–Induced Cardiovascular Consequences in Early Metabolic Impairment

Abstract: Background The complexity of the interaction between metabolic dysfunction and cardiovascular complications has long been recognized to extend beyond simple perturbations of blood glucose levels. Yet, structured interventions targeting the root pathologies are not forthcoming. Growing evidence implicates the inflammatory changes occurring in perivascular adipose tissue (PVAT) as early instigators of cardiovascular deterioration. Methods and Results We u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 108 publications
0
9
0
Order By: Relevance
“…It was found in a related survey [15] that an increase of 10 mmHg in systolic blood pressure increased the risk of coronary heart disease by approximately 20%. When the blood phosphorus level stays high for a long period, calcification of blood vessels and heart valves might be caused, which promotes the secretion of myocardial injury markers, leading to apoptosis of myocardial cells and myocardial damage and increasing the risk of cardiovascular and cerebrovascular events [16]. TG is one of the important 3 Applied Bionics and Biomechanics components that cause atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…It was found in a related survey [15] that an increase of 10 mmHg in systolic blood pressure increased the risk of coronary heart disease by approximately 20%. When the blood phosphorus level stays high for a long period, calcification of blood vessels and heart valves might be caused, which promotes the secretion of myocardial injury markers, leading to apoptosis of myocardial cells and myocardial damage and increasing the risk of cardiovascular and cerebrovascular events [16]. TG is one of the important 3 Applied Bionics and Biomechanics components that cause atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data from diabetic mouse models showed that the reduced ATP production under these circumstances is associated with mitochondrial depolarization (Veeranki et al, 2016). Nevertheless, multiple studies in animal models and humans showed that these changes are associated with increased oxygen consumption (Federico et al, 2021) similar to the observation of increased hypoxia in the PVAT/PRAT in prediabetes (Dwaib et al, 2021;Elkhatib et al, 2019;Hammoud et al, 2021). Additionally, mitochondrial carbonic anhydrases (CAs) are also among the factors contributing to cellular damage in diabetes and metabolic dysfunction (Shah et al, 2013b).…”
Section: Approaches Modulating Thermogenesis and Other Mitochondrial ...mentioning
confidence: 82%
“…LF10 Minispec Nuclear Magnetic Resonance (NMR) machine (Bruker, MA, USA) was used to assess the mouse body composition, particularly the fat-to-lean ratio, at weeks 4 and 8, as previously described [36][37][38]. NMR analysis returns masses of fat, lean, and free fluid.…”
Section: Nuclear Magnetic Resonance and Blood Glucose Measurementmentioning
confidence: 99%